Rule of Law and the Judiciary - Meier, Katja; Lorenz, Astrid; Wendel, Matthias (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The European Union is in a crisis of the rule of law which is the subject of manifold conflicts between the EU and some of its Member States. While many analyses of the crisis take a legal view, this volume expands the focus and multiplies the perspectives, bringing together views from different disciplines, countries and from outside academia with an empirical focus on Germany, Poland and the Czech Republic within the EU. The analyses provide readers with a lot of valuable expertise about the rule of law and judicial independence in the countries under study. With contributions by Dr. Lisa H. Anders | Dr. Adam Bodnar | Dr. Joachim Herrmann | Bettina Limperg | Prof. Dr. Astrid Lorenz | Katja Meier | Jan Němec, Ph.D. | Prof. Dr. Wojciech Piątek | Didier Reynders | Prof. Dr. Dr. h. c. Klaus Rennert | Prof. Dr. Werner Reutter | Prof. Dr. Anne Sanders | Prof. Dr. Dr. Ivo Šlosarčík, LL.M. | Prof. Dr. Mattias Wendel